The future of medicine: a socio-philosophical aspect - Lepskiy, M.; Utiuzh, I. H.; Pavlenko, N. V.; Утюж, Ірина Геннадіївна; Павленко, Нателла Валеріївна (My University, 2023)
The article states that health preservation is no longer a personal matter of the individual, it is, without exag- geration, an issue of national significance. Therefore, social-philosophical views of modern reforms in medicine give numerous answers to the topical issues of shaping the future of medicine. It is emphasized that the current reform in healthcare of Ukraine as well as the corresponding changes in education to reconstruct the healthcare system are characterized by randomness, unawareness of the problems crucial for the future, and of the ways to solve them. The article especially focuses on military developments as another phase of medicine development, which heals society in terms of healthcare field development jointly with the state, military sphere, and civil soci- ety. In the article, the meaning-making space of the problem field of the Ukrainian medicine’s future is defined. It is determined that the future shapes the real of modernity. The attempt has been made to justify the existential essence of the humanitarian and anthropological component of the post-capitalist reality, in particular on the basis of which humanity will invest love and care for a person. Thus, maintaining health, building public health and healthcare systems of countries have become the priority lines of the social program in the modern and future society.
Utiuzh I. H. - ORCID: 0000-0003-1152-0151; Pavlenko N. V. - ORCID: 0000-0001-5283-4945.
Keywords: COVID-19; healthcare; public health; market egocentrism; medical culture; P4medicine; military events